2021
DOI: 10.2147/ijn.s325448
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Microvesicles in Tumor Progression and Clinical Applications

Abstract: Microvesicles are extracellular vesicles with diameter ranging from 100 to 1000 nm that are secreted by tumor cells or other cells in the tumor microenvironment. A growing number of studies demonstrate that tumor-derived microvesicles are involved in tumor initiation and progression, as well as drug resistance. In addition, tumor-derived microvesicles carry a variety of immunogenic molecules and inhibit tumor response to immunotherapy; therefore, they can be exploited for use in tumor vaccines. Moreover, becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 184 publications
0
30
0
1
Order By: Relevance
“…The higher percentage of T lymphocytes may be caused by an increased number of Tregs, which was not elucidated in our work. In solid tumors, TEVs induce expansion of Tregs [ 50 ]. Similar observations were made in leukemia, increasing tumor growth and modifying TME in an autocrine manner, and modulating the vascular and stromal bone marrow niche in humans [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher percentage of T lymphocytes may be caused by an increased number of Tregs, which was not elucidated in our work. In solid tumors, TEVs induce expansion of Tregs [ 50 ]. Similar observations were made in leukemia, increasing tumor growth and modifying TME in an autocrine manner, and modulating the vascular and stromal bone marrow niche in humans [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, research on MPs for cancer treatments has increased substantially [ 160 ]. The various characteristics of MPs, such as size, surface charge and compositions, make them successful in terms of utility for inducing antitumor activity.…”
Section: Prospects Challenges and Conclusionmentioning
confidence: 99%
“…These MPs not only release drugs into the cytoplasm of TRCs, but also transport drugs into the lysosomes and nucleus, causing TRC apoptosis. Research has demonstrated objective evidence for the clinical efficacy of TMPs in patients with LC, making TMPs well tolerated in clinical practice [ 134 ].…”
Section: Clinical Applications Of Microparticles For Diagnosis Progno...mentioning
confidence: 99%